Analysis of Adaptation to Digital Transformation in Government Internal Supervision at Yogyakarta City and Sleman Regency Inspectorates - Matheus Gratiano Mali; Tri Asih Wismaningtyas; Catur Wulandari (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2024)
This study aims to examine the digital transformation adaptations undertaken by the Yogyakarta City Inspectorate and the Sleman Regency Inspectorate, functioning as Government Internal Supervisory Apparatus (APIP), and to assess how these adaptations influence the inspectorates’ supervisory roles in today’s digital era. The internal supervision process includes auditing, reviewing, evaluating, monitoring, and conducting other oversight activities to ensure that the tasks and functions of regional apparatus organizations are executed in alignment with established indicators. This qualitative descriptive research collects data through interviews, observation, and document analysis at the Yogyakarta City Inspectorate, Sleman Regency Inspectorate, and the Financial and Development Supervisory Agency (BPKP) Representative Office in the Yogyakarta Special Region. The data analysis involves data reduction, data presentation, and verification or conclusion drawing. The study specifically examines digital tools and processes such as electronic audit management systems, digital reporting platforms, and data analytics software used by the inspectorates. Results indicate that, as APIP entities both at Level 3, the Yogyakarta City and Sleman Regency Inspectorates have not yet fully integrated digital adaptations into their supervisory roles. However, both inspectorates have made notable progress, advancing from basic digitization toward digitalization and digital transformation, though the process remains incomplete. The use of these digital tools has begun to impact supervisory functions by enhancing data accuracy and streamlining some oversight activities, yet challenges remain in terms of system interoperability and user proficiency. Strong commitment from regional leadership and the inspectorates is essential to enhance regulatory readiness, budgeting, infrastructure, and human resource capabilities to achieve comprehensive digital adaptation in their supervisory functions